Escala de produção, tecnologia e desempenho da avicultura de corte em Goiás - Sartin, Karla Roberto (2016)
This study aimed to analyze production performance in poultry production at different scales of production and technologies used, using the method of ordinary least squares to develop empirical models to evaluate the productive performance of small and large poultry producers. Data were collected with an integrated industry in Goiás. The data were processed and submitted to multiple linear regression. It was found that there are factors that influence the poultry production, including the ambience of the aviary, genetics and management of birds. Through this research it was found that only two elements are integrated poultry farmer responsibility to agribusiness, the ambience and the management. Among the factors related to the ambience of greater importance is the technology absorbed by the farmer. From the empirical models built it was verified that the technology causes positive influence on almost all criteria of production of poultry production performance. It was found that the production scale, measured by per producer aviaries number is not improving productive performance factor in poultry production in Pires microregion of Rio. In all the models developed to production scale showed no significant causal relationship or relevant. These results show that this place searched the poultry production is a business opportunity for small farmers.